2018
DOI: 10.1002/jbio.201800314
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative FRET measurement based on spectral unmixing of donor, acceptor and spontaneous excitation‐emission spectra

Abstract: The spontaneous excitation-emission (ExEm) spectrum is introduced to the quantitative mExEm-spFRET methodology we recently developed as a spectral unmixing component for quantitative fluorescence resonance energy transfer measurement, named as SPEES-FRET method. The spectral fingerprints of both donor and acceptor were measured in HepG2 cells with low autofluorescence separately expressing donor and acceptor, and the spontaneous spectral fingerprint of HEK293 cells with strong autofluoresence was measured from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…To accurately analyze the signal amplification, FRET is also coupled with spectral unmixing technique to separate the signal contributions from the donor and the acceptor 62 , 63 . Although spectral unmixing has been rarely explored for CRET, we speculated that spectral unmixing could be feasible for our DAS-CRET.…”
Section: Resultsmentioning
confidence: 99%
“…To accurately analyze the signal amplification, FRET is also coupled with spectral unmixing technique to separate the signal contributions from the donor and the acceptor 62 , 63 . Although spectral unmixing has been rarely explored for CRET, we speculated that spectral unmixing could be feasible for our DAS-CRET.…”
Section: Resultsmentioning
confidence: 99%
“…where W D , W S , and W A are the contributions of the S D , S S , and S A in S DA , respectively. We also obtain (Du et al, 2016;Zhang et al, 2018;Su et al, 2019;Zhang et al, 2019)…”
Section: Theorymentioning
confidence: 83%
“…ExEm-spFRET with as few as two excitation wavelengths makes it easy to perform microscopic ExEm-spFRET imaging for single living cells. Our recent studies have demonstrated the strong robustness of ExEm-spFRET imaging (Lin et al, 2018;Su et al, 2019). We recently also performed an ExEm-unmixing-based FRET two-hybrid assay in living cells to analyze the stoichiometric information of macromolecular complexes (Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accurately analyze the signal amplification, FRET is also coupled with spectral unmixing technique to separate the signal contributions from the donor and the acceptor [74][75] . Although spectral unmixing has been rarely explored for CRET, we speculated that spectral unmixing could be feasible for our DAS-CRET.…”
Section: Das-cret In Brain Homogenatesmentioning
confidence: 99%